Environmental Sustainability and Social Justice in Tourism: Towards a Holistic Approach - Bentley, Leo (Universitas Islam Indonesia, 2024)
This study examines the intricate relationship between environmental sustainability and social justice within tourism. With the global imperative to address climate change and promote sustainable practices, the tourism industry stands at a pivotal juncture, where considerations of social equity and environmental stewardship must be intertwined. This study explores the concept of sustainable tourism development as a means of achieving environmental conservation as well as social justice objectives. Drawing on a multidisciplinary framework, this study examined the interconnectedness between environmental sustainability and social justice in the tourism context. It investigates how tourism activities impact local communities, mainly marginalized and vulnerable groups, and analyzes strategies to ensure an equitable distribution of benefits and opportunities. Emphasis is placed on initiatives that prioritize community engagement, cultural preservation, and empowerment of disadvantaged populations. The study also examined the role of stakeholders, including governments, tourism operators, NGOs, and local communities, in promoting a holistic approach to tourism management that balances environmental concerns with social equity goals. The ultimate aim of this study is to propose actionable recommendations and policy frameworks that integrate environmental sustainability and social justice imperatives into tourism planning and management. By fostering a symbiotic relationship among tourism development, environmental conservation, and social inclusion, this study envisions a more equitable and resilient tourism sector that contributes positively to both the planet and society.